Civic Literacy and Social Work Education: Results From a Multi-Site Study. Issue 1 (2nd January 2017) - McCabe, Heather A.; Hylton, Mary E.; Kooreman, Harold E.; Sarmiento Mellinger, Marcela; Day, Angelique
ABSTRACT: Given the decline in civic literacy among Americans, social work educators can no longer assume that students come prepared with the civic knowledge necessary for competent advocacy or policy practice. This article examines rates of civic knowledge among social work students at four social work education programs across the United States (U.S.). Findings indicate that although social work students score higher than the general U.S. adult population, their civic knowledge scores are still low, with nearly a third of these students falling in the failing range. Results suggest that social work students need additional content on civic knowledge.